CAF specific expression of podoplanin may be dispensable for the malignancy of malignant melanoma: brief communication - Tauch, Saskia; Kast, Bettina; Lohr, Sabrina; Kemm, Lowis; Sator-Schmitt, Melanie; Gengenbacher, Nicolas; Augustin, Hellmut; Angel, Peter (Molecular carcinogenesis, 2025)
Within the tumor microenvironment (TME), cancer-associated fibroblasts (CAFs) were shown to be an active and pivotal cell population, supporting many protumorigenic mechanisms. Podoplanin (PDPN)-positive CAFs are of special interest since their abundance correlated with a worse prognosis for patients of different cancer entities, including malignant melanoma. In this study, we applied a loss-of-function approach in an in vivo mouse melanoma model to evaluate the contribution of CAF-specific PDPN expression to melanoma formation and progression. Surprisingly, despite its prominent expression in CAFs deletion of PDPN in this cell type did neither affect the onset, nor growth of MM tumors. These data imply that PDPN expression in CAFs represents a biomarker for poor prognosis but does not serve as a useful target for stroma-directed therapy of malignant melanoma.
Erstmals veröffentlicht: 08. November 2024
Gesehen am 01.04.2025